Primary Leiomyosarcoma of the Adrenal Gland: A Case Report with Immunohistochemical Study and Literature Review - Murat Tolga Gulpinar; Asif Yildirim; Berrin Gucluer; Ramazan Gokhan Atis; Cengiz Canakci; Cenk Gurbuz; Turhan Caskurlu (Case Reports in Urology)
Primary adrenal leiomyosarcoma is extremely rare tumor. We report a case with adrenal leiomyosarcoma. Our case was a 48-year-old man who presented with lower urinary tract symptoms. Ultrasonography and magnetic resonance imaging revealed approximately 9 cm solid mass originating from right adrenal gland. He underwent right adrenalectomy. Pathology of the specimen showed histologic and immunohistochemical features of adrenal leiomyosarcoma.